DETECTION CHANGES AND ANALYSIS OF URBAN SPRAWL IN M’SILA CITY (ALGERIA): CONTRIBUTION OF SPATIAL REMOTE SENSING AND GIS - Abbas Saliha (International Journal of Innovative Technologies in Social Science, 2024)
Urban sprawl is one of the major problems facing Algerian cities, For almost half a century, urban sprawl, due to its unprecedented scale, has profoundly changed the relationship of cities to space and has given rise to the emergence of new urban forms, The monitoring and understanding of its spatial evolution remain an essential step in any approach to the sustainable development of the steppe city, local authorities do not have appropriate tools, likely to be updated regularly, to enable them to act effectively in terms of planning and spatial development, spatial remote sensing and geographic information systems (GIS) offer opportunities to overcome these difficulties. The study presented here consists of the application of a change detection technique to map and quantify the spatiotemporal spread of the city of M’sila (Algeria) during the period 1985 - 2023, using Landsat images from the years 1985, 2000 and 2023. The post-classification comparison of land use maps revealed an increase in built-up areas, especially along roads, despite this urban spatial growth, agricultural activities remain visible, which means that there is a competition between urban development and agricultural production areas is therefore evident. The objective of this study is to highlight the process of urban sprawl and the changes in land use it generates, it shows the importance of change detection methods for understanding forms of urbanization and assessing their impacts on steppe cities.